2007
DOI: 10.1029/2006wr005486
|View full text |Cite
|
Sign up to set email alerts
|

Global impacts of conversions from natural to agricultural ecosystems on water resources: Quantity versus quality

Abstract: [1] Past land use changes have greatly impacted global water resources, with often opposing effects on water quantity and quality. Increases in rain-fed cropland (460%) and pastureland (560%) during the past 300 years from forest and grasslands decreased evapotranspiration and increased recharge (two orders of magnitude) and streamflow (one order of magnitude). However, increased water quantity degraded water quality by mobilization of salts, salinization caused by shallow water tables, and fertilizer leaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
403
0
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 620 publications
(440 citation statements)
references
References 115 publications
4
403
0
10
Order By: Relevance
“…Adequate management of these areas to retain natural vegetation cover will maintain or improve water quality. Indeed, areas of high natural cover yield high quality water, with the lowest possible soil erosion, and nutrient and sediment loss (Scanlon et al, 2007).…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…Adequate management of these areas to retain natural vegetation cover will maintain or improve water quality. Indeed, areas of high natural cover yield high quality water, with the lowest possible soil erosion, and nutrient and sediment loss (Scanlon et al, 2007).…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…While important as measures, we neglected the consideration of rainfall and evapotranspiration (ET) for biofuel crops, because the effects are inherently regional and need to be discussed in the context of regional water sustainability. Scanlon et al (4) point out that ET and net water flux on agricultural lands can be greater or lesser depending upon the alternate land use and agricultural practices including tillage and fallow periods. Thus, depending upon alternate land uses compared to biofuel crops, we cannot speculate if biofuel crops will have more or less impact on the regional water supply.…”
Section: Manufacturing and Installation Of Physical Capital; Andmentioning
confidence: 99%
“…Three of the six sites are similar to the eastern study area, with similar or lower precipitation rates of 455, 500, and 605 mm/year. Recharge rates at these sites are 15, 15, and 26 mm/year, representing 3, 3, and 4% of precipitation, respectively, lower than the estimates from rain-fed agriculture in this study.<b.Recharge rates under rain-fed cropland in the eastern study area (50-120 mm/year; 8-20% of MAP) are slightly higher than recharge rates in deep sands in northwestern Senegal (30 mm/year; ~10% of MAP of 290 mm/year; Gaye and Edmunds 1996) and slightly higher than recharge rates in the Southern High Plains, USA (24 mm/year, 5% of MAP of 450 mm/year; Scanlon et al 2007b), and southwestern Niger in Africa (25 mm/year; 4% of MAP of 557 mm/ year; Favreau et al 2009). The slightly higher recharge rates may be related to higher MAP than Senegal and to the intensity of the summer monsoon in the eastern study area and more sandy soils relative to more evenly distributed summer precipitation in the Southern High Plains At rain-fed sites, concentrations and inventories of NO 3 and PO 4 are highest in the root zone (≀ 1 m) and generally much lower at depth, indicating minimal leaching of these nutrients.…”
Section: Comparison With Recharge Estimates From Previous Studiesmentioning
confidence: 99%
“…The hydrostratigraphic records trace past changes in recharge in response to variations in forcing from land-use change and climate variability (Scanlon et al , 2007aGates et al 2008;Favreau et al 2009). Unsaturated zone pore water NO 3 concentrations provide information on whether there is natural NO 3 in the profile from atmospheric deposition, as found in parts of the southwestern USA (Walvoord et al 2003), from nitrogen fixation by native vegetation, as found in Senegal (Deans et al 2005), or from mineralization and nitrification of soil organic nitrogen and over application and leaching of applied fertilizers in cropland areas (Scanlon et al 2008). Large NO 3 reservoirs in unsaturated media or in groundwater can be considered a resource for crop production, minimizing the need for fertilizer application (Deans et al 2005).…”
Section: Introductionmentioning
confidence: 99%